Strategi Pemberdayaan Kader Posyandu untuk Meningkatkan Program Gizi di Kecamatan Denpasar Utara - I Wayan Sukrayasa; IGAG. Eka Martiningsih; I Gusti Ayu Ari Agung (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
The problem of nutritional status of children in Bali Province in general and especially in Denpasar is still a problem. The presence or absence of child nutrition problems in a region not far from the contribution of the role of Posyandu cadres. The aim of this research is to know the factors related to the empowerment of cadres in the achievement of nutrition status program of children under five years old. Cross sectional analytic research design. Research location in West Denpasar District. The research time is conducted for a month. Samples of head of Posyandu cadres, as many as 83 samples. The research instrument used questionnaires on characteristics, knowledge, training, motivation of posyandu cadres and cadre empowerment strategies. Data analysis using univariate and bivariate analysis of chi square test with 95% confidence level at ? = 0.05. Data analysis shows most (63.85%) have enough level of knowledge. Most (90.36%) have already attended nutrition training. The ability of the cadre to motivate most (71.08%) includes enough categories. The result of statistical test showed that there was no correlation between cadres knowledge level (p = 0.853) and training of cadres (p = 0.418) with achievement of nutritional status program of children under five in posyandu, there is relationship of cadre ability motivated with achievement level of nutrition status program at posyandu (p = 0.009). Empowerment strategy of posyandu cadres by applying the strengths while utilizing the opportunities that exist.Keywords: Posyandu cadres, achievement of nutrition program